Development of leadership skills for IT professionals - PAVLIUK, Oksana; RASSOKHA, Anna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The relevance of the topic is determined by the high dynamism of the IT sector, which requires managers to have a unique synthesis of technical expertise and emotional intelligence. The essence of leadership competencies in IT lies in ensuring the simultaneous achievement of maximum innovation and predictable product stability. The study aimed to theoretically substantiate and investigate the psychological aspects of the development of leadership competencies of IT specialists, as well as to develop a methodology and a short training program for their improvement. Methods. The empirical study was conducted online in October 2025. The sample consisted of 80 managers and young professionals from IT companies. A set of psychodiagnostic techniques was used: T. Ehlers’ technique for diagnosing motivation for success, R. Schwarzer and M. Jerusalem’s self-efficacy scale, M. Schneider’s communicative control questionnaire test, C. Osguda’s semantic differential method, and the author’s questionnaire “Profile of IT Specialist Leadership Competencies”. Results. The study revealed a predominance of average (37%) and low (36%) levels of leadership competencies among specialists. The most critical deficits were recorded on the “Negotiation Skills” scale (60% low level) and “Activity” (60% low level), reflecting passivity and lack of energy. Correlation analysis confirmed that strategic thinking is closely related to communicative control (r = 0.649, p ≤ 0.05) and self-efficacy (r = 0.742, p ≤ 0.05). A two-day training course was developed to address the identified deficits. Conclusions. The development of leadership competencies in IT is a deeply psychological process that requires the targeted implementation of programs focused on “soft” skills (emotional intelligence, tolerance for uncertainty, negotiation skills). Training is one of the effective methods for forming holistic leadership self-awareness and developing emotional stability.